STATISTICAL ANALYSIS OF THE PHYSICAL PROPERTIES OF VARIETIES OF BEANS (Phaseolus vulgaris L.) INFLUENCED BY MATURITY STAGE (Nigerian Journal of Technology, 2018)
Physical properties of post-harvest bean seeds was studied, but the physical properties of bean seeds in response to post flowering (maturity stage) have not been fully studied; therefore, this study is aimed at evaluating the physical properties of two bean varieties (iron and honey) during their maturation stages. The bean seeds were harvested at 15, 20 and 25 days after flowering (DAF), the physical properties (length, width, thickness, average thousand seed mass, size, volume, geometric mean, sphericity, surface area, arithmetic mean, bulk density, true density, porosity, angle of repose, and the static friction coefficient (against plywood, rubber, Formica, galvanized iron, and aluminum surfaces)) in both bean varieties were evaluated. The results showed that maturity stage of the bean seeds significantly (P? 0.05) influenced all their physical properties. Over the course of a maturation time, while their porosity and angle of repose decreased, in both bean varieties, other properties were found to increase. The bean seeds true density increased from 817.75 to 1207 kg/m3 in iron bean, and 774.25 to 1144 kg/m3 in honey bean; likewise, the bulk density increased from 464.5 to 761.75 kg/m3 and 544.75 to 867.66 kg/m3 in the iron and honey bean respectively; porosity decreased from 42.15 to 36.37% in the iron bean and 34.19 to 26.41% in the honey bean. The static coefficient of friction result was; Formica (iron bean, 0.24 to 0.35; honey bean 0.22 to 0.28), aluminum (iron bean 0.31-0.37; honey bean 0.25 to 0.32), galvanized iron (iron bean, 0.35-0.44; honey bean, 0.33 to 0.39), plywood (iron bean, 0.49 to 0.58; honey bean 0.39 to 0.46), and rubber (iron bean 0.55 to 0.61; honey bean 0.43 to 0.50). While the angle of response decreased from 39.62 to 30.73o in the iron bean and 45.78 to 36.84o in the honey bean. Furthermore, the results show that the ideal period for harvest, processing and handling of the two bean seeds is 20 to 25 days after anthesis, since the seeds will be having maximum dry weight and higher viability. Data gotten from this result is useful in the design and development of harvesting, handling and processing equipment.